Algae Coral Interactions: Mediation of Coral Settlement, Early Survival, and Growth by Macroalgae - Maypa, Aileen P.; Raymundo, Laurie J. (Silliman Journal, 2022)
Degraded coral reefs are often colonized by macroalgae, which can impede coral reestablishment. However, impacts of abundant macroalgae have not been well-established for juvenile stages of coral. This study examined the effects of morphology and chemistry of four species of macroalgae on the early life history of the coral Pocillopora darnicornis in laboratory aquaria. Morphologies of Sargassum polycystum and Laurencia papillosa significantly inhibited larval settlement (S. polycystum and L. papillosa: <30% settlement, vs. algae-free control: 60% settlement), while their exudates enhanced settlement (S. polycystum: 67% ± 6%; L. papillosa: 71% ± 4%; control: 20% + 4%). Neither morphology nor exudates of Halirneda opuntia and Peyssonnelia rubra significantly affected larval settlement. Juveniles survived less in aquaria containing H. opuntia, while survival was facilitated in aquaria with P. rubra. Growth was also affected differentially; colonies growing with L. papillosa (5 ± 0.8 polyps per colony) and S. polycystum (4 ± 0.1 polyps/colony) were significantly smaller at three months than those growing with H. opuntia (6 ± 0.9 polyps/colony) and P. rubra (6 ± 0.6 polyps/colony). These data suggest that the effects of macroalgae on early life history stages of corals are complex and long-term, and vary between species.